2021
DOI: 10.1177/09544089211008052
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni convection in the transient flow of hybrid nanoliquid thin film over a radially stretching disk

Abstract: Within a magnetohydrodynamic environment, Marangoni convection (Thermocapilarity effect) in an unsteady thin film of hybrid nanoliquid flow over a disk has been discussed. A set of simplified Navier-Stokes equation using boundary layer theory is written in order to model the above mentioned flow situation. The dissipative effects caused by viscosity and magnetic field have been incorporated in temperature-balance equation. A suitable choice of transform variables facilitate a system of ordinary differential eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Marangoni convection frequently occurs in metallurgy, painting and drying, 4 semiconductor production, 5 and production of silicon wafers. It is dominant form of convection in microgravity region or the reduced gravity regions 6,7 . Yu et al 8 simulated the effects of concentration dependent capillary convection in an annular pool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marangoni convection frequently occurs in metallurgy, painting and drying, 4 semiconductor production, 5 and production of silicon wafers. It is dominant form of convection in microgravity region or the reduced gravity regions 6,7 . Yu et al 8 simulated the effects of concentration dependent capillary convection in an annular pool.…”
Section: Introductionmentioning
confidence: 99%
“…It is dominant form of convection in microgravity region or the reduced gravity regions. 6,7 Yu et al 8 simulated the effects of concentration dependent capillary convection in an annular pool. It was concluded that smaller values of soluto-capillary Reynolds number creates steady axisymmetric flow; however, for higher values, a second vortex emerges in the interior of circular pool.…”
Section: Introductionmentioning
confidence: 99%
“…Nandi and Kumbhakar [24] analyzed the flow of tangent hyperbolic nanofluid flowing over a wedge under Hydromagnetic assumptions. Tripathi [25] discussed the flow of hybrid nano-liquid past an elongating disk by considering the effect of Marangoni convection. He found that the use of blade-shaped nano particles in hybrid nano-liquid result in maximum heat transfer at the disk surface.…”
Section: Introductionmentioning
confidence: 99%
“…Ganesh et al 6 discussed Marangoni convection in the flow of normalAl 2 normalO 3-nanofluid under the influence of the magnetic field. Recently, Tripathi 7 discussed the Marangoni convection in the thin film of hybrid nanofluid over a disk and showed that an increase in interfacial tension tends to accelerate the velocity of the hybrid nanoliquid. In the last few years, it has been established that for certain fluids, surface tension is not necessarily a decreasing function of temperature.…”
Section: Introductionmentioning
confidence: 99%